ESTUDO DO MR E RT DE MISTURAS EM CONCRETO ASFÁLTICO ENVELHECIDAS PREPARADAS COM DIFERENTES TIPOS E TEORES DE LIGANTES - Budny, Jaelson; Hartmann, Diego; Bock, André L.; Rozek, Thiago d. M.; Specht, Luciano P. (Salão do Conhecimento, 2013)
Resumo